A Panel-corrected Standard Error (PCSE) Framework to Estimate Capital Structure and Banking Performance within the Tunisian Context - Zidi, Manel; Hamdi, Helmi (International Journal of Economics and Financial Issues, 2024)
The objective of this article is to empirically examine the effect of financing structure on the market share of banks, and their performance in Tunisian banks. To this end, we gathered financial statements of ten commercial banks over the period 2012-2019, and we employed the panel-corrected standard error (PCSE) regression. The empirical results show that the bank capital structure measured by the equity to total assets ratio negatively affects bank performance while the debt to total assets ratio can be a robust and positive driver of bank performance. Through this research, we recommend to Tunisian commercial banks to reduce their operating costs through a better management of their resources, and to find cheaper sources of financing such as increasing equity. We also recommend to Tunisian commercial banks to diversify further their revenues in order to enhance their performance and to generate more profits.